ANALISIS EFEKTIVITAS LAMPU LALU LINTAS PERSIMPANGAN JALAN SOEKARNO HATTA JALAN DURIAN - JALAN SIGUNGUNG - Saputra, Parada Afkiki Eko (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2024)
Abstract The intersection of Jalan Soekarno Hatta - Jalan Durian - Jalan Sigungung is one of the four intersections with quite a high traffic volume in the city of Pekanbaru. The intersection of Jalan Soekarno Hatta- Jalan Durian- Jalan Sigungung currently uses a three-phase signal cycle. Currently, at this intersection, conflicts often occur between vehicles passing through this intersection. This is very dangerous for motor vehicle drivers. Conditions in the morning when people carry out activities when going to work, in the afternoon, precisely at lunch time, and also in the afternoon, precisely when it is time for workers to go home, the traffic volume at this intersection is quite high. So under these conditions, traffic jams also become a routine sight due to the problem of when the green signal has expired, vehicles are still queuing, resulting in long queues and from an economic perspective, transportation results in wastage of fuel for drivers. From the results of the analysis, it was found that the traffic volume (Q) was 1067 pcu/hour, the capacity value (C) was 876.18 pcu/hour, the degree of saturation (DJ) was 0.726, the provisions for the DJ value itself were in accordance with PKJI 2014, namely that it could not be more > 0.85 The intersection delay value (T) is 44.6 pcu/sec, and the queue length (PA) value is around 32.265 m. The Saturday period at 17.00 - 18.00 WIB is the maximum traffic flow with a saturation value of 0.726. while the cycle time obtained was 118 seconds with the traffic volume obtained being 1067 pcu/hour using 3 phases between east and west approaches with red lights from the north and south. For phase 1 itself, the green time and red time are 35 seconds and 77 seconds. The level of service at each approach can be determined through the average delay at each approach. Where the relationship between average delay and level can be seen in the table. Based on the calculation of the average delay value for each approach, a delay value of 44.6 pcu/sec is obtained with service level E, unstable flow.